English Public Speaking Training for Vocational College Students in Madiun - Pratiwi, Damar Isti; Budiastuti, Riana Eka; Amumpuni, Rengganis Siwi; Arifianto, Teguh (STMIK Royal, 2024)
Many vocational college graduates got difficulties during job interview process. Therefore, this community service activity aims to enhance vocational college students’ English communication skills, especially in public speaking, during the job interview process. It was done online through a Zoom meeting, which was opened for vocational college students in Madiun City, East Java. The activity was done in May 2024, starting from the preparation, implementation, and evaluation process. It ran well and benefited vocational college students by equipping them with and broadening their knowledge regarding the job interview process. The participants’ feedback was positive, in which the survey results showed that the community service activity improved their public speaking skills and confidence. The participants also provided a rough description of the job interview process through mock interviews. It is hoped that a similar activity will be carried out continuously in the future. Keywords: English, Public Speaking, Training, Vocational College, Vocational Students Banyak lulusan kampus vokasi yang kesulitan saat menjalani proses interviu kerja. Untuk itu, kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kemampuan berkomunikasi bahasa Inggris mahasiswa vokasi terutama pada public speaking di proses wawancara kerja. Kegiatan ini dilaksanakan secara daring melalui Zoom meeting yang dibuka bagi mahasiswa vokasi di kota Madiun, Jawa Timur. Kegiatan ini dilakukan pada bulan Mei 2024 yang dimulai dari proses persiapan, pelaksanaan dan evaluasi. Kegiatan berjalan dengan lancar dan bermanfaat bagi para mahasiswa vokasi dalam memperlengkapi dan memperluas wawasan mereka mengenai proses wawancara kerja. Umpan balik dari para peserta menunjukkan nilai positive dimana hasil survei menunjukkan bahwa kegiatan pengabdian masyarakat ini meningkatkan kemampuan public speaking para peserta dan rasa percaya diri mereka. Para peserta juga mendapatkan gambaran kasar mengenai proses wawancara kerja melalui kegiatan mock-interview. Diharapkan bahwa kegiatan sejenis dapat diadakan berkelanjutan di masa mendatang.Kata kunci: Bahasa Inggris, Public Speaking, Pelatihan, Kampus Vokasi, Mahasiswa Vokasi